Teori Filsafat Humanistik dalam Pembelajaran Matematika - Hanter Manik; Agustina C B Sihite; Maria Martha Manao; Suryati Sitepu; Tutiarny Naibaho (Universitas Muhammadiyah Enrekang, 2022)
Philosophy is a field of science that invites people to think deeply to seek the truth. One of the sciences that is often applied in our daily life is mathematics. The philosophy of humanistic psychology put forward by humanist philosophers includes views on human rights, views on human freedom and autonomy, self-concept, and individual self and self-actualization. Mathematics is the fruit of thoughts or ideas generated by humans. This paper is the result of a study. This paper discusses the development of the philosophy of humanism which is applied to mathematics learning.